2020
DOI: 10.1158/1078-0432.ccr-19-3322
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anti-TNF with Decreased Survival in Steroid Refractory Ipilimumab and Anti-PD1–Treated Patients in the Dutch Melanoma Treatment Registry

Abstract: Purpose: Unleashing the immune system by PD-1 and/or CTLA-4 blockade can cause severe immune-related toxicity necessitating immunosuppressive treatment. Whether immunosuppression for toxicity impacts survival is largely unknown.Experimental Design: Using data from the prospective nationwide Dutch Melanoma Treatment Registry (DMTR), we analyzed the association between severe toxicity and overall survival (OS) in 1,250 patients with advanced melanoma who were treated with immune checkpoint inhibitors (ICI) in fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 23 publications
1
93
1
Order By: Relevance
“…In addition to opportunistic infections, another theoretical risk of use of immunosuppressant is the loss of antitumor immunity. One report Open access has described poorer outcomes for patients treated with anti-TNF agents±steroids in comparison to steroids alone, 17 although this has not been described in most other cases nor obviously noted in this report. 18 In fact, preclinical data demonstrates that with anti-TNF therapy toxicity management can be uncoupled from efficacy and that TNF blockade might even have positive effects on anticancer control.…”
Section: Discussioncontrasting
confidence: 49%
“…In addition to opportunistic infections, another theoretical risk of use of immunosuppressant is the loss of antitumor immunity. One report Open access has described poorer outcomes for patients treated with anti-TNF agents±steroids in comparison to steroids alone, 17 although this has not been described in most other cases nor obviously noted in this report. 18 In fact, preclinical data demonstrates that with anti-TNF therapy toxicity management can be uncoupled from efficacy and that TNF blockade might even have positive effects on anticancer control.…”
Section: Discussioncontrasting
confidence: 49%
“…This is not surprising, in view of the common underlying mechanism of irAEs and anti-tumor responses ( 48 ). It is important to consider that the patients at increased risk of irAEs could also be the patients deriving the most benefit from ICIs and that aggressive or early irAE management could compromise ICI efficacy ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, questions remains as to the role anti-TNF may play on promoting or suppressing the antitumor efficacy of ICIs. 41 Currently, two trials addressing this question have obtained contradictory results with one study demonstrating infliximab abrogated the survival advantage given by ICI treatment 47 while another study reported improved survival of patients with cancer. 27 Considering the known dual role of TNF in tumor development, addressing this question is of the utmost importance before generalizing the use of infliximab in the clinic.…”
Section: Discussionmentioning
confidence: 99%